CORPORATE CULTURE IMPACT ON THE BUSINESS OF AN ENTERPRISE - Filipova, Milena (Revista Inclusiones, 2020)
The phenomenon of corporate culture has been an object of great attention by the part of theory and practices since the 1970s -1990s and is still particularly actual nowadays. The understanding of corporate culture enables the formation of adequate knowledge and skills by managers that can be applied in practice and contribute to the improvement of efficiency of the management of an enterprise. The main objective of this work is to clarify the essence of corporate culture, to study the connection between corporate culture and the efficiency of an enterprise and to identify the key elements of the efficient corporate culture. The main results expected are identified key elements of the efficient corporate culture that can be used by the managers to improve the business of a company.The main research methods used in the study are content analysis, method of comparison, intuitive and systematic approach, method of analysis and synthesis.